(untitled) (Bangladesh Heart Journal, 2017)
Background: Peripheral arterial disease (PAD) is a marker of increased risk for cardiovascular events and of poorer prognosis in patients with coronary artery disease (CAD). The prevalence of unknown PAD amongst patients with ACS varies between studies according to the mode of diagnosis. Aims: To evaluate the prevalence of peripheral arterial disease (PAD) in diabetic ACS patients with or without tobacco user by using ankle brachial index (ABI).We also assess the probable predictors of PAD among these patients. Methodology: This prospective observational study was conducted in the Department of Cardiology, Ibrahim Cardiac Hospital and Research Institute, Dhaka, Bangladesh starting from 1st January 2016 to 30th April 2016 over a period of four months. A total of 60 patients were studied. They were grouped on the basis of their smoking habit. Diabetic patients with ACS and tobacco user (smoke and smoke less) in group I and without tobacco user in group II. Results: The mean age of the studied patients was 56.63 ± 8.95 years, range from 25-90 years. 73.30% was male and 26.70% was female. Twenty three patients of tobacco user in group-I (n=30) had peripheral artery disease and ten patients of group-II (n=30) had peripheral artery disease. It was statistically significant (p=0.003). Conclusion: There is correlation between peripheral arterial disease and coronary artery disease. Diagnosis and supervision of patients with PAD is important for preventing the local progression of the disease and effective secondary prevention of future coronary and cerebrovascular events. Bangladesh Heart Journal 2017; 32(1) : 3-9